2013
DOI: 10.5152/jaem.2013.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ice and Lidocaine- Prilocaine Cream Mixture in the Reduction of Pain During Peripheral Intravenous Cannulation in Emergency Department Patients

Abstract: Objective:We aimed to compare the efficacies of ice, lidocaine-prilocaine mixture cream and the classical method in reduction of the pain observed during intravenous cannulation, which is the most frequently performed procedure in emergency departments and to define the most effective method. Material and Methods: One hundred-twenty patients who applied to the emergency department of Uludag University Faculty of Medicine were included in this presented study. Cannulations were performed after one minute applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In the literature, there are fewer studies using nonpharmacological interventions to reduce the pain of PIC insertion than studies using drugs for this purpose (Aygun et al, ; Suren et al, ; Yilmaz & Gunes, ; Zempsky et al, ). Most of the studies were performed in healthy adults (Aygun et al, ). To be used widely in clinics, nonpharmacological methods for PIC insertion pain control must be easy to teach and use, be inexpensive, be working fast and have few or no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are fewer studies using nonpharmacological interventions to reduce the pain of PIC insertion than studies using drugs for this purpose (Aygun et al, ; Suren et al, ; Yilmaz & Gunes, ; Zempsky et al, ). Most of the studies were performed in healthy adults (Aygun et al, ). To be used widely in clinics, nonpharmacological methods for PIC insertion pain control must be easy to teach and use, be inexpensive, be working fast and have few or no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐pharmacological approaches used in acute pain control include physical and behavioral techniques 4,12 . Approaches such as directing the attention elsewhere, 4,12 vibration, 13 cold application, 9 and the Valsalva maneuver 14 are examples of non‐pharmacological methods used in the control of acute pain developing in connection with invasive procedures in children. Although there are some data to support each of these methods, no single optimal method has been found to relieve pain.…”
Section: Figmentioning
confidence: 99%
“…Pharmacological approaches include topical anesthetic creams and vapocoolant sprays 7,8 . Even though these methods are known to be effective in pain control, they are also known to have a large number of side effects 9‐11 . Recently therefore, non‐pharmacological methods for the control of acute pain in children have been increasingly preferred because of the lower probability of side effects.…”
Section: Figmentioning
confidence: 99%
“…Pharmacological methods such as emla cream, ethyl chloride or lidocaine have long been used to control the pain and discomfort felt during peripheral intravenous catheterisation (Burke, Vercler, Ra'Net, Desmond, & Rees, ; Hendry, Checketts, & McLeod, ; Winfield et al., ), but although pharmacological methods have been found to be effective in pain control, disadvantages from the patient's point of view have also been reported, such as the possibility of side effects and extra time and cost (Aygün et al., ; Labrague, Rosales, Rosales, & Fiel, ). For this reason, a need has been reported for nonpharmacological methods for the control of pain in peripheral intravenous catheterisation which are easy to use, do not have the possibility of side effects and are inexpensive and nontime‐consuming in use (Canbulat, Ayhan, & İnal, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years therefore, there has been a steady increase in the use of nonpharmacological methods in the relief of pain. Many such methods are in use to relieve pain during peripheral intravenous catheterisation, such as cold application (Aygün et al., ), the use of the Buzzy device, which is in the shape of a bee and which applies cold via ice wings and vibration via a motor (Şahiner, İnal, & Akbay, ), and diverting the attention (Canbulat, İnal, & Sönmezer, ; Yoo, Kim, Hur, & Kim, ). Apart from these, studies have reported the use of the Valsalva manoeuvre to reduce interventional pain (Kumar, Budur, & Odappa, ; Mohammadi, Pajand, & Shoeibi, ; Wallace, Allen, Lacroix, & Pitner, ).…”
Section: Introductionmentioning
confidence: 99%